ANALISIS STRATEGI GURU KELAS 3 DALAM MEMBINA KEMAMPUAN MEMBACA SISWA DENGAN KETERBATASAN KONSENTRASI DI SDN BAHAGIA 03 - Savira Salsabila; Sani Aryanto; Yohamntin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the strategies employed by third-grade teachers to fosterreading skills among students with concentration limitations at SDN Bahagia 03. Thisresearch used a qualitative approach with a case study method. Data were collectedthrough observation, interviews, and documentation. The findings revealed thatteachers implemented various strategies such as using visual media, reading aloudmethods, and individual approaches to enhance students’ focus. The study alsofound that teachers’ emotional support played a crucial role in motivating studentswith concentration challenges. These findings are expected to serve as a referencefor developing adaptive reading instructional strategies.